Gaze diversion affects cognitive and motor performance in young adults when stepping over obstacles - Cho, HyeYoung; Romine, Nathaniel Lee; Barbieri, Fabio Augusto [UNESP]; Rietdyk, Shirley (Elsevier, 2019)
Background: In many common multi-tasks, vision is used for two or more of the tasks, such as viewing cars, traffic signals, and the sidewalk curb at a crosswalk. Research Question: How does gaze diversion affect adaptive locomotion in young adults? Methods: Seventeen young adults completed a simple reaction time (RT) task while (1) standing and (2) during the approach to an obstacle on an 8 m walkway. Participants pressed a remote switch in response to a light cue (activated once during approach phase). The light cue was located either (1) on the obstacle (gaze diverted to obstacle) or (2) at eye level (gaze diverted away from obstacle). A gait baseline task with no RT task was included. Results: An interaction was observed (task (standing versus walking) by gaze location (on versus away from obstacle), p = 0.01), where RT was not affected by the gaze location in the standing task, but RT was longer when gaze was diverted away from the obstacle in the gait task. Furthermore, trail foot placement was closer to the obstacle when the gaze was diverted away from the obstacle (p = 0.002), which increased risk of tripping. Significance: Gaze diversion did not affect cognitive performance in the standing task, as information regarding the obstacle was not relevant for the standing task. However, completing a simple discrete visual cognitive task during obstacle crossing impaired both cognitive and gait performance, but only when gaze was diverted away from the obstacle. The impaired performance is likely due to the larger amount of structural interference when gaze was diverted away from the obstacle. These findings highlight the critical role of vision during the approach phase to an obstacle.
Keywords: adaptive gait; gaze diversion; Reaction time; vision